2022
DOI: 10.3390/su142013214
|View full text |Cite
|
Sign up to set email alerts
|

Improving Selected Chemical Properties of a Paddy Soil in Sabah Amended with Calcium Silicate: A Laboratory Incubation Study

Abstract: In Malaysia, the main constraints of rice yield and productivity are infertile soils and poor management practices because these soils are characterized by low pH, low nutrient availability, low organic matter, and high exchangeable Al and Fe ions, due to high rainfall and hot temperatures. Thus, an incubation study was conducted to determine the optimum amount of calcium silicate (HmbG brand) to improve the soil pH, electrical conductivity (EC), exchangeable Al, available P, and cation exchange capacity (CEC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 53 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The results showed that the samples were predominately silicate soils rich in iron and aluminum. According to Chong et al [66], the high content of exchangeable Al and Fe ions is mainly due to the high temperatures and heavy rains resulting in low soil pH, low nutrient availability, and low organic matter content. A significant difference in SiO 2 percentage was noted between the FF and CF, confirming quartz particles' predominance in the R'mel soils.…”
Section: X-ray Fluorescence Analysismentioning
confidence: 99%
“…The results showed that the samples were predominately silicate soils rich in iron and aluminum. According to Chong et al [66], the high content of exchangeable Al and Fe ions is mainly due to the high temperatures and heavy rains resulting in low soil pH, low nutrient availability, and low organic matter content. A significant difference in SiO 2 percentage was noted between the FF and CF, confirming quartz particles' predominance in the R'mel soils.…”
Section: X-ray Fluorescence Analysismentioning
confidence: 99%